Peculiarities of forensic-medical and related researches in the case of moving vehicle and bicyclist contact - Plevinskis, P. V. (Journal of Education, Health and Sport, 2016)
Plevinskis P. V. Peculiarities of forensic-medical and related researches in the case of moving vehicle and bicyclist contact. Journal of Education, Health and Sport. 2016;6(8):241-248. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60410 http://ojs.ukw.edu.pl/index.php/johs/article/view/3753 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. UDC 616 – 001.4/.6 – 036.88 – 079.6 Peculiarities of forensic-medical and related researches in the case of moving vehicle and bicyclist contact P. V. Plevinskis Odessa National Medical University, Odessa, Ukraine Abstract Forensic-medical examiners face with the cases of car and bicyclist contact in their practice. The main goal of examination is to determine the variant of car, bicycle and bicyclist’s body contact, that’s why it is necessary to determine the mechanism of bodily injuries forming, taking to consideration various trace-forming objects, which can contribute to injuries’ forming on the bicyclist’s body. It is possible to classify the type of traffic accidents according to the types and quantity of the traumatic objects for the bicyclist’s body and according to the sequence of contacting of the vehicle, bicycle and bicyclist’s body. Not all questions could be solved by forensic-medical examiner (on example, questions about sequence and phases of bodily injuries forming), that’s why in such cases it is necessary to perform complex forensic-medical and transport-trasological examination with obligatory studying of the vehicle, which participated in traffic accident, bicycle, driven by the injured person, clothes and shoes of the injured bicyclist, bicyclist’s bodily injuries and results of the scene of incident inspection. All bicyclist’s bodily injuries could be divided on three large groups: bodily injuries, which have formed in the result of primary contact of the bicyclist’s body and parts of the car; bodily injuries, which have formed in the result of body’s throw on the defined parts of the car; bodily injuries, which have formed in the result of bicyclist’s contact with the road. Algorithm of research in the case of forensic-medical examination of injured bicyclist was created, which predicts cooperation of forensic-medical and transport-trasological examiners and gives a possibility for more effective solving of forensic tasks. Key words: forensic-medical examination, bicyclsit’s injury, algorithm of complex examination, types of car and bicycle contact.